Making yourself heard at the customer again – how songwriting facilities sucessfull storytelling - Peter Mathias Fischer; Johannes Flecker (Marketing Review St.Gallen, 2016)
As the quote above from Philip Pullman, a British writer, highlights, it is innate to human behavior that we are keen on telling as well as listening to stories. Stories not only enable us to better store and retrieve information (Fournier 1998). Even more critically, they also result in "proper pleasure" being cathartic (Holt 2003).
Keywords: 650